Media Pembelajaran Edugame Arabic Berbasis Mobile Application - Tri Heru, Ahmanto; Fahmi, Arif (INFORMAL: Informatics Journal, 2024)
Technological innovations are increasingly developing, making the world of educational media also developing, one of which is multimedia applications in the form of educational games. It is hoped that learning media can provide benefits to students so that their interest in learning increases. Arabic tends to be a scary language and is often disliked by many students because it seems difficult to learn. Apart from that, learning media that is still manual and monotonous often becomes a problem because it causes students to get bored. It is hoped that the digital learning media created can create an interesting and conducive learning atmosphere so that learning activities become enjoyable because of the availability of images and sound to facilitate the learning process. Arabic edugame is a learning media created using the SDLC (System Development Life Cycle) method with the waterfall model. Starting with analyzing, designing, coding and testing the application. Arabic edugame was designed using Adobe Flash Professional CS6, Adobe Photoshop, Corel Draw The results of the mobile application-based Arabic edugame learning media trial show that Arabic edugame has game theme features, an attractive design and can deliver the material well to attract students' interest in learning Arabic with an average of 57.61%.